КАУЗАЛЬНОСТЬ КАК ТИП СЕМАНТИЧЕСКИХ ОТНОШЕНИЙ В МЕДИА ДИСКУРСЕ (Eurasian Journal of Philology Science and Education, 2015)
The article investigates causality as one of the major semantic types in discourse. Formal explicit means help to form cause effect relations in discourse. The ways of verbalization of implicit causal meaning is also under focus of the paper.